The anticoagulant effects of warfarin and the bleeding risk associated with its use in patients with chronic thromboembolic pulmonary hypertension at a specialist center in Japan: a retrospective cohort study. (June 2017) - Jujo-Sanada, Takayuki; Tanabe, Nobuhiro; Sakao, Seiichiro; Sugiura, Toshihiko; Sekine, Ayumi; Nishimura, Rintaro; Suda, Rika; Naito, Akira; Miwa, Hideki; Yamamoto, Keiko; Sasaki, Akane; Matsumura, Akane; et al.
Patients with chronic thromboembolic pulmonary hypertension (CTEPH) require lifelong anticoagulation therapy. However, the bleeding risk and recurrence of venous thromboembolism (VTE) in CTEPH patients who are administered warfarin have not been adequately evaluated. The purpose of this study was to evaluate the risk of clinically relevant bleeding, recurrent VTE, and clinical worsening in patients with CTEPH who were administered warfarin. The clinical records of 72 patients with CTEPH who regularly visited our institution and were administered warfarin were retrospectively reviewed between 1 January 2011 and 31 December 2015. We investigated the incidence of clinically relevant bleeding events, recurrent VTE, and hospitalization for the deterioration of pulmonary hypertension or right heart failure (RHF) during the observation period. The mean observation period for the 72 patients was 3.60 ± 1.60 person-years. Clinically relevant bleeding, RHF, and recurrent VTE occurred in 21 (29.2%), eight (11.1%), and three (4.2%) of 72 patients, respectively, and the incidence rates for these events were 8.1%/person-year, 3.1%/person-year, and 1.2%/person-year, respectively. The incidence rates for the major and non-major bleeding events were 5.0%/person-year and 3.9%/person-year, respectively. The incidence of clinically relevant bleeding events was 20.8%/person-year during medical treatment with a soluble guanylate cyclase stimulator. One of 35 patients (2.9%) during the post-pulmonary endarterectomy period experienced hemoptysis during observation period (> 6 months after pulmonary endarterectomy). No bleeding events occurred during the post-balloon pulmonary angioplasty period. In conclusion, warfarin effectively prevents VTE recurrence in CTEPH patients, but its effects may be associated with a considerable bleeding risk.